Analysis of peripheral amyloid precursor protein in Angelman Syndrome. Issue 9 (21st June 2016) - Erickson, Craig A.; Wink, Logan K.; Baindu, Bayon; Ray, Balmiki; Schaefer, Tori L.; Pedapati, Ernest V.; Lahiri, Debomoy K.
Abstract : Angelman Syndrome is a rare neurodevelopmental disorder associated with significant developmental and communication delays, high risk for epilepsy, motor dysfunction, and a characteristic behavioral profile. While Angelman Syndrome is known to be associated with the loss of maternal expression of the ubiquitin‐protein ligase E3A gene, the molecular sequelae of this loss remain to be fully understood. Amyloid precursor protein (APP) is involved in neuronal development and APP dysregulation has been implicated in the pathophysiology of other developmental disorders including fragile X syndrome and idiopathic autism. APP dysregulation has been noted in preclinical model of chromosome 15q13 duplication, a disorder whose genetic abnormality results in duplication of the region that is epigenetically silenced in Angelman Syndrome. In this duplication model, APP levels have been shown to be significantly reduced leading to the hypothesis that enhanced ubiquitin‐protein ligase E3A expression may be associated with this phenomena. We tested the hypothesis that ubiquitin‐protein ligase E3A regulates APP protein levels by comparing peripheral APP and APP derivative levels in humans with Angelman Syndrome to those with neurotypical development. We report that APP total, APP alpha (sAPPα) and A Beta 40 and 42 are elevated in the plasma of humans with Angelman Syndrome compared to neurotypical matched human samples. Additionally, we found that elevations in APP total and sAPPα correlated positively with peripheral brain derived neurotrophic factor levels previously reported in this same patient cohort. Our pilot report on APP protein levels in Angelman Syndrome warrants additional exploration and may provide a molecular target of treatment for the disorder. © 2016 Wiley Periodicals, Inc.